Formulasi Sediaan Salep Ekstrak Minyak Atsiri Daun Jeruk Purut (Citrus Hystrix DC.) terhadap Jamur Candida Albicans - Ni Putu Diah Saputri; Gusti Ayu Rai Saputri; Selvi Marcellia (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The purpose of this study was to formulate essential oils in ointment preparations with different bases and to determine the physical properties and antifungal activity against Candida albicans. The essential oil of kaffir lime leaves was obtained by distillation using the water distillation method and the raw material of fresh kaffir lime leaves was 1.5 kilograms which was then identified with Sudan III reagent and formulated in ointment preparations. The ointment is made with FI, FII, and FIII base formulations with an active substance concentration of 7%. The FIII ointment base had the best evaluation results and was continued for antifungal testing against Candida albicans. From the research results obtained % yield of essential oil of kaffir lime leaves is 1.533%. The results of the phytochemical identification test showed positive results with the formation of an even red color in the solution. The results of the evaluation of the ointment preparations showed that FIII had the best evaluation results and continued antifungal testing with a positive control of 2% miconazole nitrate cream. The average diameter obtained is 8.43 mm and is included in the medium category. The results of the Shapiro Wilk normality test showed that the research data was normally distributed and homogeneous, then the One-Way ANOVA test was carried out and a significance value of P<0.05 was obtained, and the LSD test showed a significant difference seen from the significance value obtained P<0.05.